OCCUPATIONAL SAFETY IMPROVEMENT EFFORTS ON THE VESSEL OWNED BY PT. DIAN CIPTAMAS AGUNG SITE BERAU - Barasa, Larsen; Togatorop, Agus; Bagaskoro, Bagaskoro; Silitonga, Daniel (Dinasti International Journal of Management Science, 2021)
PT. Dian Ciptamas Agung is a company engaged in the shipping industry as a provider of freight services by using the vessel and barge tugboat. Based on the data on the existing problems discussing the work accident on the vessel owned by PT. Dian Ciptamas Agung and the efforts made by the company in minimizing the work accident that occurred. The purpose of this research is to know the sources of work accidents that occur in order to improve the safety of work on vessels owned by PT. The great. The research was conducted by processing the data from investigative reports, the year of events news from 2018-2019 period. This shipping company needs to pay attention to the things that cause a work accident on the vessel so it can be done and pay attention to things that drive the crew to more discipline in working on the vessel